A Guide for Obtaining Aerial Photographs and their Costs - Tomar, M. S. (Indian Forester, 1972)
Many State Forest Departments and other Organizations are increasingly interested in using aerial photographs for natural resources survey and mapping. Many queries regarding the procedure of obtaining aerial photographs and their costs are received from various Forest Departments in the country. This note, based on the informations collected from Survey of India and other sources,is intended as a general guide for obtaining aerial photographs and their costs. All indents for aerial photography should be placed with Surveyor General of India, Dehra Dun. The cost of photography, will depend on several factors such as scale and year of photography, agency which took the aerial photographs, type of photography, etc.